Qawmī Madrasah Education in Bangladesh: Safeguarding Islamic Traditions and Navigating Modern Challenges - Md Mahdi Hasan; Bhirawa Anoraga (Universitas Islam Internasional Indonesia, 2026)
This paper examines qawmī madrasah education in Bangladesh as a distinctive site for traditional Islamic scholarship, where the preservation of religious authority is continuously negotiated alongside the demands of modern educational structures. Drawing on qualitative fieldwork conducted in four qawmī madrasahs, including semi-structured interviews with 30 participants, classroom observations, and engagement with relevant scholarly, policy, and media sources, this study explores the perspectives of students, teachers, parents, and institutional authorities. The paper argues that the central challenges facing qawmī madrasahs are not merely the result of curricular limitations, but are rooted in their commitment to preserving the authority, authenticity, and transmission of Islamic knowledge, as understood by their ʿulamāʾ (traditional Islamic scholars). Qawmī students’ aspirations are closely tied to the pursuit of ʿilm (religious knowledge) and engagement in daʿwa (religious outreach), reflecting a broader moral and religious orientation that is often reinforced by family expectations, as many parents enroll their children in qawmī madrasahs to cultivate religious commitment, moral discipline, and future Islamic scholarship. However, a significant structural limitation emerges from the lack of formal recognition across the different stages of qawmī education. While students may complete the highest level of study, their earlier qualifications remain unrecognized within the national educational framework, creating barriers to entry into general universities, limiting access to a wide range of employment opportunities beyond the qawmī sphere, and restricting prospects for higher studies abroad. The findings further show that pedagogical practices, institutional autonomy, and limited curricular integration intersect in shaping both opportunities and constraints within the system. Crucially, resistance to reform is closely tied to concerns among the ʿulamāʾ regarding state intervention, particularly the fear that any external regulation may compromise their epistemic and institutional autonomy. The study concludes that meaningful engagement requires a coherent alignment between curriculum, certification, and institutional practice, developed through negotiated frameworks that preserve the internal logic of qawmī education while expanding students’ access to broader educational and social pathways.